Structural stability theory and practice : buckling of columns, beams, plates, and shells - Jerath, Sukhvarsh (Wiley, 2021)
"Structures fail mainly due to material failure or because of structural instability. An understanding of structural stability is a special branch of engineering mechanics of importance to structural engineers whose job is to design safe structures. In a structure, a small change in load could cause a large change in displacement. If the change in displacement is large enough, instability could lead to a total collapse of the entire structure. The study of structural stability examines how a structure passes from a stable state to an unstable state, the stability of different structural members and systems, and how theory translates into design methods implemented in design specifications. All major international design specifications include provisions based on stability theory"--